Toward pharmacy-based smoking cessation services in Nigeria: Knowledge, perception and practice of community pharmacists (2021)
INTRODUCTION Worldwide, tobacco smoking is one of the leading causes of avoidable deaths. In Nigeria, there is currently no clinical guidelines for tobacco dependence treatment. However, globally, pharmacy-based smoking cessation intervention has been associated with improved cessation rates and quality of life. This study aims at assessing the knowledge and perception of community pharmacists about smoking cessation and tobacco harm reduction as well as barriers to the practice of pharmacybased smoking cessation intervention. METHODS A cross-sectional survey was carried out among 104 community pharmacists, between August and December 2019, using a self-administered paper questionnaire. Data entering, cleansing, and analysis were done using IBM SPSS (version 23). Descriptive statistics including frequencies and percentages were used to summarize the data. RESULTS Thirteen pharmacists (12.5%) were providing smoking cessation services. One-tenth (10.6%) of the pharmacists were aware of tobacco harm reduction. The majority (89.4%) were willing to attend smoking cessation training. Among the respondents, 65 (62.5%) had poor knowledge regarding smoking cessation and tobacco harm reduction. Lack of knowledge and skills were reported by all (100%) as a barrier to providing the service. However, 101 (97.1%) community pharmacists agreed that smoking cessation treatment is an important role of pharmacists. CONCLUSIONS A suboptimal level of knowledge of smoking cessation and tobacco harm reduction was noted among the community pharmacists. However, they believed smoking cessation intervention is an important role of pharmacists. It is advocated that smoking cessation training should be included as part of the Pharmacists’ Council of Nigeria Mandatory Continuing Professional Development Training. Thus, it is imperative to establish basic national smoking cessation guidelines that can be functional towards reducing mortality and morbidity associated with tobacco smoking in Nigeria.